High performance liquid chromatographic method for Iso-a-Acids - Khatib, Alfi; Kim, Hye Kyong; Wilson, Erica G.; Verpoorte, Robert (Taylor & Francis Group, 2006)
Using pure trans/cis-isocohumulone, trans/cis-isohumulone, and trans/cisisoadhumulone an isocratic HPLC system has been developed for quantitation of these compounds in hop extracts and beers. The mobile phase contains acetonitrile-water- H3PO4 (50 : 50 : 0.01, v/v/v) and is used with a Phenomenex Hypersil 5 m C18 column 250 4.6 mm, flow rate 1.5mL/min. Baseline separation of all 6 isomers was achieved with a total run time of 25 min. The UV spectrum of these pure compounds using this system are quite different. The effect of different mobile phase compositions on separation was investigated as well as the chromatographic parameters, detection limit, and linearity.